PENERAPAN MODEL FLIPPED CLASSROOM BERBASIS PODCAST DALAM PEMBELAJARAN AKIDAH AKHLAK : STUDI KOMPARATIF EFEKTIVITAS KOGNITIF DAN AFEKTIF - Ilyas Rozak Hanafi; Muhamad Asror; Rofi'udin Rofi'udin; Muhamad Qomarudinul Huda; Ninik Muhajiroh (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2026)
ABSTRACT The research gap in Akidah Akhlak learning indicates that the learning process is still dominated by conventional methods focusing on knowledge transfer, which have not been optimal in developing students’ affective aspects. Studies on the Flipped Classroom generally emphasize cognitive outcomes, while the integration of podcast media in Akidah Akhlak learning and the simultaneous examination of its effectiveness on both cognitive and affective domains remain limited. This study aims to examine the effectiveness of a podcast-based Flipped Classroom model compared to conventional learning models in improving students’ cognitive and affective achievements in Akidah Akhlak subjects. The study employed a quantitative approach with a quasi-experimental design using a Non-equivalent Control Group Design. The sample consisted of experimental and control classes selected through cluster random sampling. Data were collected through learning outcome tests for the cognitive domain and Likert scales for the affective domain, then analyzed using the Independent Sample t-test with SPSS 26.0. The results showed that the experimental class achieved a higher cognitive mean score (86.5) compared to the control class (74.2), along with an 18% increase in affective outcomes, with a significance value of 0.002 (<0.05). The findings conclude that the podcast-based Flipped Classroom model is more effective in improving students’ cognitive and affective learning outcomes. ABSTRAK Kesenjangan dalam penelitian pembelajaran Akidah Akhlak menunjukkan bahwa proses pembelajaran masih didominasi metode konvensional yang berfokus pada transfer pengetahuan sehingga belum optimal dalam mengembangkan aspek afektif siswa. Penelitian tentang Flipped Classroom umumnya hanya berfokus pada aspek kognitif, sementara integrasi media podcast dalam pembelajaran Akidah Akhlak serta pengujian efektivitasnya secara simultan pada ranah kognitif dan afektif masih sangat terbatas. Penelitian ini bertujuan untuk menguji efektivitas model Flipped Classroom berbasis podcast dibandingkan dengan model pembelajaran konvensional dalam meningkatkan capaian kognitif dan afektif siswa pada mata pelajaran Akidah Akhlak. Metode yang digunakan adalah pendekatan kuantitatif dengan desain eksperimen semu tipe Non-equivalent Control Group Design. Sampel terdiri dari kelas eksperimen dan kelas kontrol yang dipilih melalui cluster random sampling. Data dikumpulkan melalui tes hasil belajar untuk ranah kognitif dan skala Likert untuk ranah afektif, kemudian dianalisis menggunakan uji Independent Sample t-test berbantuan SPSS 26.0. Hasil penelitian menunjukkan bahwa kelas eksperimen memperoleh rata-rata kognitif 86,5 lebih tinggi dibandingkan kelas kontrol 74,2, serta peningkatan afektif sebesar 18%, dengan nilai signifikansi 0,002 (<0,05). Simpulan penelitian ini menunjukkan bahwa model Flipped Classroom berbasis podcast lebih efektif dalam meningkatkan hasil belajar kognitif dan afektif siswa.